ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL SPLDV BERORIENTASI PISA DENGAN KONTEN CHANGE AND RELATIONSHIP PADA KELAS VIII SMP UNISMUH MAKASSAR - Ahmad Syamsuadi; Muh Fadli Darmadi; Awi Dassa (Universitas Muhammadiyah Makassar, 2021)
This study aims to determine student errors in solving PISA-oriented SPLDV questions with change and relationship content in class VIII SMP Unismuh Makassar based on the Newman error procedure. This type of research uses a qualitative approach with descriptive methods. Data collection techniques used were giving tests and interviews. The instrument used was a written test in the form of a description of two numbers adapted from the PISA questions and interviews of students who were selected as research subjects to ensure mistakes made when solving the questions. The researcher chose four students as research subjects from 19 students of class VIIIA 1 based on the most mistakes made to be interviewed. The data analysis technique was carried out by the stages of data reduction, data presentation, data verification and drawing conclusions. Student error analysis refers to errors with the Newman stage which consists of 4 categories, namely errors in understanding the problem, errors in transforming the problem, errors in processing skills and errors in writing the final answer. The results showed that the most errors were made by FQ students. The research subjects who were then interviewed were SM on the type of understanding error, ST on the type of transformation error, SP on the error type of process skills and SK on the type of error in writing the final answer.